2013
DOI: 10.1021/nn403198a
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of S-Layer Anisotropy: pH-Dependent Nanolayer Orientation for Cellular Micropatterning

Abstract: We have developed a tunable, facile, and reliable cell patterning method using a self-assembled crystalline protein monolayer that, depending on its orientation, can exhibit either cell adhesive (cytophilic) or cell repulsive (cytophobic) surface properties. Our technique exploits, for the first time, the inherent biological anisotropy of the bacterial cell wall protein SbpA capable of interacting with its cytophilic inner side with components of the cell wall, while its outer cytophobic side interacts with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 58 publications
(76 reference statements)
1
37
0
Order By: Relevance
“…[ 22 ] In fact, S-layers have already been proven to be a stable biomaterial under harsh denaturation conditions including treatment with ethanol (<80%), elevated temperatures (<70 °C) and pH shifts (pH > 3). [ 17,23 ] Another advantage of using S-layer proteins as a biointerface is the elimination of unspecifi c binding of biomolecules such as serum proteins and antibodies, thus also preventing unwanted cell-to-surface interactions. This means that it is possible to selectively modify and functionalize the protein nanolayers with affi nity capture probes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 22 ] In fact, S-layers have already been proven to be a stable biomaterial under harsh denaturation conditions including treatment with ethanol (<80%), elevated temperatures (<70 °C) and pH shifts (pH > 3). [ 17,23 ] Another advantage of using S-layer proteins as a biointerface is the elimination of unspecifi c binding of biomolecules such as serum proteins and antibodies, thus also preventing unwanted cell-to-surface interactions. This means that it is possible to selectively modify and functionalize the protein nanolayers with affi nity capture probes.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 ] Additionally, the pH dependent re-orientation of SbpA monolayers featuring opposing cytophobic or cytophilic surface properties was recently applied for cell patterning using micro molding in capillaries (MIMIC). [ 17 ] Furthermore, specifi c functional domains have already been introduced in S-layer proteins to foster the immobilization of biocatalysts, fl uorescent biomarkers and nanoparticles, while still maintaining their self-assembly properties. [ 18 ] An example of the implementation of specifi c functional domains includes the recombinant fusion protein rSbpA/ZZ, which contains the protein A-binding site for the effi cient capture of antibodies (IgG) and has been used as a specifi c adsorbent in extracorporeal blood purifi cation.…”
mentioning
confidence: 99%
“…The outermost envelope possessing oriented self-assembly of proteins are not restricted only to prokaryotic bacterial species but also found in archaea and virus [22]. The comprehensive literature has been documented on the biochemical aspects, self-assembling properties and genetic framework of surface layer proteins but their technical utilization is under the stage of infancy till date [18].…”
Section: Concept Of Biomimetics Based On Surface Layer Proteinsmentioning
confidence: 99%
“…Interestingly, it was shown that a self-assembled layer, depending on whether the inner or outer side is exposed to the aqueous environment, can exhibit against cells in tissue cultures either cell adhesive (cytophilic) or cell repulsive (cytophobic) surface properties, respectively. The different orientation and function of the S-layer protein can simply be achieved by altering the recrystallization protocol from a basic ( pH 9; resulting in an outer smooth cytophobic side) to an acidic ( pH 4; resulting in an inner rough cytophilic surface pattern) condition [105].…”
Section: S-layer Proteinsmentioning
confidence: 99%